1998
DOI: 10.1016/s0376-8716(98)00101-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on drug use and abuse/dependence in male and female twins

Abstract: Twins were recruited through alcohol and drug treatment programs. With structural equation modeling, genetic and environmental estimates were obtained for use and DSM-III abuse/dependence of sedatives, opioids, cocaine, stimulants, and cannabis as well as any illicit drug. Analyses were conducted separately for males and females. Models included thresholds based on population prevalence of use or abuse/dependence and ever having been in treatment. Genetic influences were found for most measures. They were gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
129
1
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(143 citation statements)
references
References 52 publications
11
129
1
2
Order By: Relevance
“…5 The heritability of abuse/dependence was relatively low for sedatives and opiates, but for psychostimulants such as amphetamines, it was as high as cocaine. 6 The primary site of biological activity of methamphetamine (METH) is the dopamine transporters in the brain. METH is taken into cytosol by dopamine transporters on the synaptic terminals of dopamine neurons, and endogenous dopamine is concurrently released through the transporters by carrier-exchange mechanisms, which results in a robust increase in the dopamine concentration in the synaptic clefts.…”
Section: Introductionmentioning
confidence: 99%
“…5 The heritability of abuse/dependence was relatively low for sedatives and opiates, but for psychostimulants such as amphetamines, it was as high as cocaine. 6 The primary site of biological activity of methamphetamine (METH) is the dopamine transporters in the brain. METH is taken into cytosol by dopamine transporters on the synaptic terminals of dopamine neurons, and endogenous dopamine is concurrently released through the transporters by carrier-exchange mechanisms, which results in a robust increase in the dopamine concentration in the synaptic clefts.…”
Section: Introductionmentioning
confidence: 99%
“…15 No entanto, esse único estudo utilizou e pequena amostragem (31 MZ e 24 DZ), não podendo concluir se os resultados foram devidos a viés de seleção. Os estudos para dependência de outras drogas encontraram diversos valores para a herdabilidade entre elas, [16][17][18][19][20][21][22] tendo nos extremos a menor herdabilidade específica para sedativos em mulheres (30%) 20 e a maior para abuso de cocaína em mulheres (79%). 21 De uma maneira geral, pode-se afirmar a presença de componente genético em todas as dependências de drogas.…”
Section: Estudos Em Gêmeosunclassified
“…Studies based on twin (e.g., Grove et al, 1990;Kendler, Karkowski, Corey, Prescott, & Neale, 1999;Kendler, Karkowski, Neale, & Prescott, 2000;Tsuang et al, 1996;van den Bree, Johnson, Neale, & Pickens, 1998) and adoptive (e.g., Cadoret, Winokur et al, 1996;Cadoret, Yates, Troughton, Woodworth, & Stewart, 1996;Yates, Cadoret, Troughton, & Stewart, 1996) samples have confirmed that while shared environmental factors may play a role in the initiation of substance use, genetic factors are the primary source of familial resemblance for illicit SUDs such as dependence, abuse, or a combination of abuse/ dependence. Univariate estimates of the heritability of illicit substance abuse and dependence did vary across substance, ranging from 25% to 79%, with most in the 55-75% range.…”
Section: Genetic Influences On Illicit Substance Use Abuse and Depementioning
confidence: 99%